Detection of line segments - Tomczyk, Arkadiusz (Wydawnictwo Politechniki Łódzkiej, 2014)
In the paper a method of line segment detection in the images is presented. It bases on existing LSD approach which was designed to be a parameterless technique dedicated to analysis of real world scenes. In consequence it encounters problems with other types of images, e.g. medical images, where the characteristic of the structures may be completely different. The method proposed in this work allows to tune its parameters for that characteristic and thus allows to achieve satisfactory results also for medical data. The effect of the approach is illustrated with mammographic images.